The Role of Wilayatul Hisbah in Enforcing Order on Juvenile Deviant Behavior: A Qualitative Study in Banda Aceh - Munif, Aqil; Jarnawi, Jarnawi; NK, Mahdi (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
This study aims to describe the role of the Wilayatul Hisbah in regulating deviant activities among adolescents in the Blang Padang Field area of Banda Aceh and to identify the inhibiting factors in the implementation of such enforcement. Deviant activities in this context include behaviors that contradict Islamic sharia norms, such as promiscuity, violations of dress codes, and activities potentially leading to juvenile delinquency. This research employs a qualitative approach, with data collected through observations, in-depth interviews with Wilayatul Hisbah officers, community leaders, and adolescents in the area, as well as document analysis. The findings reveal that the Wilayatul Hisbah plays a strategic role as a sharia law enforcement body through routine patrols, guidance programs, and preventive measures. However, the effectiveness of these efforts is hindered by a shortage of personnel, limited operational budgets, and resistance from certain groups of adolescents. These findings underscore the importance of synergy among the Wilayatul Hisbah, families, educational institutions, and the wider community to foster a social environment that supports adolescent character development in accordance with Islamic values.